Social significance of trunk use in captive Asian elephants. Issue 4 (4th July 2017) - Yasui, Saki; Idani, Gen'ichi
Abstract : Tactile behaviour plays an important role in maintaining social relationships in several mammalian species. Touching with the tip of the trunk is a common social behaviour among Asian elephants ( Elephas maximus ). This is considered an affiliative behaviour; however, few studies have investigated it in detail. Therefore, this study aimed to determine whether this is an affiliative behaviour and whether it has other functions. We directly observed a group of captive female Asian elephants in Thailand. We found that the elephants usually touched each other with their trunks shaped in a U (U-type) or S (S-type) shape. The S-type shape was observed mainly when the elephants touched the lips of other elephants; however, this behaviour was occasionally observed in agonistic or play contexts, where it appeared to be a threat or dominant behaviour, particularly amongst adults. In contrast, the U-type shape was more frequently observed when the elephants were disturbed, where it appeared as a gesture for reassurance. We found that the U-type touch on the genitals may be used for interacting with neonates. Therefore, we suggest that despite the S-type touch having a tactile component, it may be a rare behaviour in Asian elephants that is similar to visual threat displays in other mammals. However, the U-type touch is similar to social grooming behaviour in primates or flipper rubbing in dolphins, and can be used as an indicator of affiliative relationships. Asian elephants change the shape of their trunk while touching others depending on their motivation and the situation, thereby demonstrating that the nuances of trunk use can assist in understanding the social relationships between individuals.